1999
DOI: 10.1097/00004694-199911000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Sixty cases of congenital scoliosis over a 13-year period were studied. The female:male ratio was 1.4:1. The deformity usually presented itself first either at 2 or 8-13 years of age. A positive family history was present in five cases, and parental consanguinity was observed in 40% of patients. Five patterns of deformity were recognized. Hemivertebra was the most common type, and unilateral unsegmented bar with contralateral hemivertebra was the most severe and most progressive pattern of deformity. Thoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Congenital scoliosis (CS) is a rare type of spinal deformity secondary to congenital vertebral malformation (CVM) with an incidence of 0.1% approximately [1]. Usually, the severity of the congenital scoliosis is dependent on CVM type, location and number, as well as the patients’ age [24]. Previous studies have demonstrated that most congenital scoliosis may be progressive [57].…”
Section: Introductionmentioning
confidence: 99%
“…Congenital scoliosis (CS) is a rare type of spinal deformity secondary to congenital vertebral malformation (CVM) with an incidence of 0.1% approximately [1]. Usually, the severity of the congenital scoliosis is dependent on CVM type, location and number, as well as the patients’ age [24]. Previous studies have demonstrated that most congenital scoliosis may be progressive [57].…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, patients present with large deformities that require more significant procedures. [2] Statistics indicate that the female:male ratio is 1.4:1, [3] meaning that more than half of patients are women. Therefore, many patients who are treated with surgery will face pregnancy and delivery.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Studies reported that 3.4% families had at least 2 members with a congenital spine deformity [6] and 1 positive family history was present in 5 cases. [7] Wynne-Davies [8] identified a sibling recurrence risk of 2% to 3% in multiple vertebral defect patients from a study of 300 patients with CS. Multigenerational CS in 1 family was also reported.…”
Section: Introductionmentioning
confidence: 99%